2008
DOI: 10.1016/j.rmed.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Improvements with tiotropium in COPD patients with concomitant asthma

Abstract: Patients with COPD and concomitant asthma achieve spirometric improvements with tiotropium along with symptomatic benefit as seen by reduced need for rescue medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 22 publications
(25 reference statements)
0
59
0
8
Order By: Relevance
“…Thus far, the only placebo-controlled study in ACOS has shown that once daily tiotropium bromide significantly improved FEV 1 , peak expiratory flow rates and decreased use of rescue medication [Magnussen et al 2008]. So far, no further clinical studies on long-acting anticholinergics or β sympathomimetics have been performed.…”
Section: Long-acting Bronchodilatorsmentioning
confidence: 99%
“…Thus far, the only placebo-controlled study in ACOS has shown that once daily tiotropium bromide significantly improved FEV 1 , peak expiratory flow rates and decreased use of rescue medication [Magnussen et al 2008]. So far, no further clinical studies on long-acting anticholinergics or β sympathomimetics have been performed.…”
Section: Long-acting Bronchodilatorsmentioning
confidence: 99%
“…Another RCT was designed to determine the spirometric effects of tiotropium in COPD patients with concomitant asthma. 24 The results showed that the patients with COPD and concomitant asthma achieved spirometric improvements with tiotropium treatment along with symptomatic benefits as seen by a reduced need for rescue medication. To reduce the heterogeneity of different trials, we also selected only data from asthma patients without other lung diseases.…”
Section: Discussionmentioning
confidence: 96%
“…The only clinical trial performed to date in patients with ACOS studied the effects of tiotropium in 472 individuals with concomitant COPD and asthma. Improvements in lung function and a reduction in rescue medication were observed with tiotropium [35]. However, the main interest in differentiating ACOS from COPD lies in the different response to ICS.…”
Section: Treatmentmentioning
confidence: 99%